Coping with Stress While Awaiting Covid-19 Test Results: Survey of Israeli Air Force Personnel. (2nd October 2022) - Gordon, Shirley; Garbi, Dror; Ben Bassat, Shahar; Shapira, Shachar; Shelf, Leah
Abstract: belowThe uncertainty involved in the period of waiting for the COVID-19 test results often accompanied by anxiety. The purpose of the present survey was to examine the level of emotional distress among Air Force personnel awaiting COVID-19 test results. The survey included 284 participants, 62% male (mean age = 24.3, SD = 7.61). Participants received an online questionnaire that covered the following topics: type of isolation (e.g., home, military unit, a military inpatient facility); COVID-19 status (e.g., awaiting testing, tested); a self-evaluation questionnaire of health, and a Generalized Anxiety Disorder questionnaire (GAD-7). At the time of the survey, over 50% were waiting to be tested or to receive the test results. The degree of distress was higher in the group that was in isolation at home than at a military medical facility. Women had higher levels of anxiety than men. Soldiers in compulsory military service had higher levels of distress than career personnel. The isolation environment provided in a military facility had a beneficial effect on the soldiers' mental state. An accumulation of several stressors such as the operation assignments and the marital and financial status may increase the likelihood of distress.